1996
DOI: 10.1128/aac.40.9.2126
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal elimination of ofloxacin enantiomers in the rat: evidence of a carrier-mediated process

Abstract: The aim of this work was to examine the mechanism involved in intestinal elimination of the two optical isomers of ofloxacin in the rat. An intestinal segment was isolated in situ and perfused with saline, while drug solution was administered via the carotid artery. Blood samples and intestinal effluents were collected and analyzed by a high-performance liquid chromatography method. We observed saturable and stereoselective intestinal elimination of the ofloxacin enantiomers. The elimination process favored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Previous research supported that other fluoroquinolones are subjected to active efflux (Griffiths et al. , 1994; Rabbaa et al. , 1996).…”
Section: Discussionmentioning
confidence: 86%
“…Previous research supported that other fluoroquinolones are subjected to active efflux (Griffiths et al. , 1994; Rabbaa et al. , 1996).…”
Section: Discussionmentioning
confidence: 86%
“…Later studies in rats confirmed intestinal secretion of parenterally administered ciprofloxacin, fleroxacin, and sparfloxacin and demonstrated that coadministration of ciprofloxacin or pefloxacin significantly reduced the in vivo intestinal clearance of ofloxacin, suggesting a common transport system [40,41]. Subsequent inhibition of in vivo intestinal elimination of ofloxacin by verapamil and quinidine indicated possible involvement of the ABC transporter family, for example, MDR1, in this process [41]. In vitro studies conducted in Caco-2 cell monolayers, a model system for human intestine, demonstrated verapamil-sensitive secretion of grepafloxacin and sparfloxacin, also pointing to ABC transporter involvement in the intestinal secretion of FQs [42,43].…”
Section: Active Transport/facilitated Diffusion and Fq Dispositionmentioning
confidence: 88%
“…Therefore, passive diffusion across the GI epithelium and other systemic tissue barrier epithelia should be a negligible component of their [37][38][39]. Later studies in rats confirmed intestinal secretion of parenterally administered ciprofloxacin, fleroxacin, and sparfloxacin and demonstrated that coadministration of ciprofloxacin or pefloxacin significantly reduced the in vivo intestinal clearance of ofloxacin, suggesting a common transport system [40,41]. Subsequent inhibition of in vivo intestinal elimination of ofloxacin by verapamil and quinidine indicated possible involvement of the ABC transporter family, for example, MDR1, in this process [41].…”
Section: Active Transport/facilitated Diffusion and Fq Dispositionmentioning
confidence: 95%
“…Although interaction between parent ABZ and P-glycoprotein does not occur (Merino et al, 2002), enantioselective transport of ofloxacin and talinolol by P-glycoprotein has been shown in the process of intestinal elimination (Rabbaa et al, 1996;Hanafy et al, 2001). Thus, different intestinal metabolism, interactions and transport of ABZSO could determine the proportions of the enantiomers in faeces and this could explain the different enantiospecific dispositions between plasma and faeces.…”
Section: Discussionmentioning
confidence: 96%